2021
DOI: 10.30587/umgeshic.v1i2.3492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perception of Ease, Security, and Features on Decision to Use Digital Wallet Gopay

Abstract: Nowadays, many platforms are emerging-based financial services fintech to support electronic money activities in Indonesia. One of the fintechs is  digital payment, fintech provides online payment system services through digital wallets. The development of fintech, especially digital wallets in Indonesia, in the last 5 years has increased in shaping consumer behavior. With the existence of a digital wallet, the opportunities for consumers to make online payments are wider in providing convenience for transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In line with the results of Shiliha (2022), which illustrates the relationship between the relationship between security fintech variables and customer decisions in saving, the primary data obtained states that as many as 67.6% of respondents strongly agree with the influence of the relationship between religiosity variables and customer decisions in saving. Supported by the results of research by Sinta & Sukaris, (2021), it is revealed that the relationship between a person's Fintech Security variables can affect interest in saving.…”
Section: Security Of Saving Decisionsmentioning
confidence: 90%
See 1 more Smart Citation
“…In line with the results of Shiliha (2022), which illustrates the relationship between the relationship between security fintech variables and customer decisions in saving, the primary data obtained states that as many as 67.6% of respondents strongly agree with the influence of the relationship between religiosity variables and customer decisions in saving. Supported by the results of research by Sinta & Sukaris, (2021), it is revealed that the relationship between a person's Fintech Security variables can affect interest in saving.…”
Section: Security Of Saving Decisionsmentioning
confidence: 90%
“…The application of fintech makes it easy for the public to transact; digital banks can operate without an office but must have a head office that only operates as a monitoring team or operational supervisor of the digital bank. Strengthened by Sinta & Sukaris, (2021), digital banks must have official security standards, take part, and be able to provide improvements to the progress of financial institutions in the future. The public is urged to be careful in its use because fintech access itself is vulnerable to data security.…”
Section: Security Fintechmentioning
confidence: 99%
“…Penelitian ini dutujukan untuk menganalisa elemen penentu empiris variabel dalam keputusan masyarakat menjadi wisatawan halal lokal. (Teori deduktif) 29 berargumentasi bahwasanya adanya fintech memberikan efektivitas serta kenyamanan untuk masyarakat. Teriring adanya proteksi wisatawan digital membuat sesuai dengan prinsip fintech pariwisata halal, bentuk penelitian ini menggunakan penilaian kuantitatif dengan pengumpulan data simple random sampling serta pertimbangan peluang untuk setiap populasi yang dipilih sebagai sampel menggunakan 30 rumus Lemeshow(Tidak terhitung pupolasi,96 responden).…”
Section: Metode Penelitianunclassified